MARKETING ANALYSIS OF BANANA CHIPS (Case Study of Mindari MSMEs in Noelbaki Village, Kupang Tengah District, Kupang Regency) - Erni Djawa; Maria Bano; Maximillian M.J. Kapa (Undana Press, 2026)
This study aims to analyze marketing channels, marketing margins, and marketing efficiency of banana chips produced by UMKM Mindari in Noelbaki Village, Central Kupang District, Kupang Regency. A quantitative descriptive approach was employed, using primary data collected through observations, interviews, and questionnaires distributed to 50 respondents, as well as secondary data obtained from the enterprise’s sales records. The analysis focused on identifying marketing channel structures, marketing costs and margins, and the level of marketing efficiency. The results reveal two marketing channels, namely a direct channel from producers to consumers and an indirect channel involving retailers. The direct channel generates no marketing margin because the entire price paid by consumers is received by producers, indicating a highly efficient marketing system. In contrast, the indirect channel produces a marketing margin of IDR 5,000 per package, equivalent to 20% of the consumer price, with producers receiving 80% of the final price. The marketing efficiency value of the indirect channel is 8.5%, suggesting that this channel is still considered reasonably efficient. Overall, the findings indicate that the direct marketing channel is the most efficient and provides greater benefits for producers. These results imply that strengthening direct marketing strategies while maintaining indirect channels can enhance market coverage, competitiveness, and income sustainability for small and medium-sized agro-processing enterprises.